A COMPARISON OF THE EFFECTS OF PROBLEM-BASED LEARNING AND PROJECT-BASED LEARNING ON VOLLEYBALL UNDERHAND PASSING SKILLS - Imelda Br Sitepu; Saipul Ambri Damanik (Universitas Negeri Medan, 2026)
This study aims to examine the differences in the effects of the Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models on improving basic underhand passing skills in volleyball among eighth-grade students. The method used was a quasi-experimental study with a two-group pretest-posttest design. The study population comprised all eighth-grade students at SMP Negeri 1 Salapian. A purposive sampling technique was used to select 60 students, who were divided into two experimental groups (30 students each for the PBL and PjBL models). Data were collected using a motor skills portfolio assessment rubric. Data analysis was conducted using paired and unpaired t-tests at a 5% significance level. The results showed a significant effect for both learning models, with the calculated t-value for the PBL model being 8.925 > the critical t-value of 2.05 (p = 0.000) and for the PjBL model being 8.169 > the critical t-value of 2.05 (p = 0.000). The study’s conclusion indicates that the implementation of the PBL model yields significantly more effective results than the PjBL model in improving underhand passing skills in volleyball among eighth-grade students at State Junior High School 1 Salapian.